Rancang Bangun Sistem Inventory (Studi Kasus: UD. Asia Pratama Pekanbaru) - Sesilia Rosaulina, Sesilia; Sihotang, Ceria Monika; S, Syahril (NUANSA INFORMATIKA, 2024)
UD Asia Pratama Pekanbaru, a trading company in the building industry, is facing problems in managing inventory which is still manual, causing inefficiencies and inaccurate data. This research aims to design and implement an efficient and effective web-based inventory management system. The system development method uses the Waterfall model, including requirements analysis, design, implementation and testing. Data was collected through interviews with employees and analysis of documents related to inventory. The research results show that the system developed can increase inventory management efficiency, with real-time stock management features, recording of incoming and outgoing goods, and accurate reporting. User testing and evaluation shows that the system is acceptable and meets UD Asia Pratama's needs in overcoming inventory problems.